2011
DOI: 10.5194/hessd-8-10707-2011
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

El-Niño southern oscillation and rainfall erosivity in the headwater region of the Grande River Basin, Southeast Brazil

Abstract: Abstract. Relationships between regional climate and oceanic and atmospheric anomalies are important tools in order to promote the development of models for predicting rainfall erosivity, especially in regions with substantial intra-annual variability in the rainfall regime. In this context, this work aimed to analyze the rainfall erosivity in headwaters of Grande River Basin, Southern Minas Gerais State, Brazil. This study considered the two most representative environments, the Mantiqueira Range (MR) and Pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Wet seasons or years in Rwanda coincide with El Niño and dry seasons are observed during La Niña phenomena (Ngarukiyimana et al, 2018). Previous research in China (Chen and Zha, 2018), US (D'Odorico et al, 2001) and Brazil (Mello et al, 2011) indicated that average rainfall erosivity is stronger during El Niño events and weaker during La Niña events. At monthly temporal resolution, the dataset comprises both dry, normal and wet conditions.…”
Section: Spatio-temporal Representativity Of the Rainfall -Erosivity Datamentioning
confidence: 85%
“…Wet seasons or years in Rwanda coincide with El Niño and dry seasons are observed during La Niña phenomena (Ngarukiyimana et al, 2018). Previous research in China (Chen and Zha, 2018), US (D'Odorico et al, 2001) and Brazil (Mello et al, 2011) indicated that average rainfall erosivity is stronger during El Niño events and weaker during La Niña events. At monthly temporal resolution, the dataset comprises both dry, normal and wet conditions.…”
Section: Spatio-temporal Representativity Of the Rainfall -Erosivity Datamentioning
confidence: 85%
“…This in turn affects the sediment mobilization associated with erosive rainfall events. In particular, Mello et al [99] found a correlation between erosive events in Brazil and sea surface temperature of the Equatorial Pacific region (El Niño-3.4). This means that in years with significant ENSO events, rainfall regime tends to increase in this region, which implies increased rainfall erosivity and, so, sediment rates.…”
Section: River Sediment Discharge Historical Reconstructionmentioning
confidence: 99%
“…Ward et al (2016) found by simulation that El Nino events tend to increase not only flood prevalence but also flood duration. In Brazil, El Nino event tends to increase soil erosivity [19]. Since the main stream of the Arau catchment flows through the heart of the City of Padang, its functions as the source of domestic water and for drainage are vital for the city.…”
Section: Land Use Changementioning
confidence: 99%